Corrective phosphate application as a practice for reducing oxidative stress and increasing productivity in sugarcane - Silva, Ariane Márcia; Oliveira, Emídio Cantídio; Willadino, Lilia; Freire, Fernando; Rocha, Alexandre (Revista Ciência Agronômica, 2019)
Corrective phosphate application increases the levels of phosphorus (P) in the surface layer of the soil, stimulates plant root growth and increases the volume of soil exploited for water and nutrient uptake, which may reduce abiotic oxidative stress in sugarcane. The aim of this study was to evaluate the productivity and the response of the antioxidant enzyme system in sugarcane when grown in soil that received corrective phosphate application, using doses and sources of P of varying solubility. The experiment was conducted under field conditions in the southern Forest Zone of the State of Pernambuco, Brazil. The treatments were arranged in a randomised block design, in a (4 × 3) +1 factorial scheme with four replications. The factors consisted of a control (with no phosphate application) and the doses (50, 100, 200 and 300 kg P2O5 ha-1 ) and sources (reactive natural phosphate, triple superphosphate and sugarcane press mud) of P applied during the pre-planting stage of the plant cane cycle. The P content of the leaf tissue was considered adequate, and was not influenced by the phosphate application. Phosphate application at an estimated dose of 150 kg P2O5 ha-1 reduced antioxidant enzyme activity and increased shoot dry matter (SDM) by 25.0% and stalk productivity by 8.5%. Superoxide dismutase (SOD) showed the highest positive correlation coefficient with the other antioxidant enzymes, and a negative correlation with SDM, and can be used to evaluate abiotic stress that promotes reductions in sugarcane productivity.